Oral administration of heat-inactivated Escherichia coli during suckling alleviated Salmonella typhimurium-derived intestinal injury after rat weaning - Cui, Minghui; Tang, Guangfu; Yan, Fang; Wang, Shunshan; Wang, Xi; Yao, Junhu; Xu, Xiurong (Frontiers in Immunology, 2023)
Introduction Newly weaned animals are susceptible to a wide range of microbial infections taking a high risk of developing post-weaning diarrhea. Trained immunity is the capacity of the innate immune system to produce a stronger and non-specific response against a secondary infection after the inflammatory response caused by previous stimulus has returned to normal state. The objective of this study was to evaluate if the heat-inactivated Escherichia coli (IEC) as an immunostimulant on suckling pups elicits a protective effect on the intestine of post-weaning rats challenged with Salmonella Typhimurium (S.Typhimurium). We adapted a newborn rat model for this purpose. Methods Sixty newborn pups were randomly separated into two groups: IEC group (n =30) orally administrated IEC during suckling, while the CON group received orally the same dose of saline. Both of the two group challenged with various doses of S.Typhimurium after experiencing a 4-week resting period. Twelve of individuals were selected to detect the survival rate, and ten of the rest were necropsied 48 hours post-challenge. Results and Discussion The results showed that oral administration of IEC during suckling alleviated the injury in ileal morphology induced by post-weaning S.Typhimurium infection via increasing the levels of two tight junction proteins [zonula occluden-1 (ZO-1) and Occludin-1] and several secreted proteins (Lysozyme, Mucin-2, and SIgA) in the intestinal mucosa. Furthermore, the pre-stimulation with IEC significantly increased cytokines tumor necrosis factor-alpha (TNF- α) and interleukin-1 beta (IL-1 β) expressions in an enhanced secondary reaction way after experiencing a 4-week resting period. This implicated the possible involvement of trained immunity. The 16S rDNA sequence results showed that pre-stimulation with IEC decreased the abundance of Clostridia, Prevotella, Christensenellaceae_R-7_group and Parabacteroides after intestinal infection of S.Typhimurium. Our results confirmed that the previous oral administration of IEC had a protective effect on S.Typhimurium-induced intestinal injury in weaned rats by inducing a robust immune response. The present study suggested a new strategy for preventing intestinal infection of newborn animals.